Acerca del diseño especulativo del espacio arquitectonico: experiencias, metaforas y abstraccion (2019)
The acts of imagining, creating and projecting are con-cepts of pure speculation, since, at the beginning of the process, conscientious architects do not know with cer-tainty what is going to be achieved, but with the objective of always improving what exists. Architects such as Peter Eisenmann, Frank Gehry, Mies van der Rohe and Peter Zumthor aim to speculatively propose formal solutions in their projects based on abstract, metaphorical and expe-riential concepts.